(untitled) (Architecture Image Studies, 2025)
Hydrogen refueling stations require stable communication protocols for real-time monitoring and control. The Modbus TCP, which is used in existing hydrogen refueling stations, has limitations owing to a lack of time synchronization and event search functions. This study addressed these issues by applying the IEC 61850 communication standard to hydrogen refueling stations. Using IEC 61850 data modeling techniques, we designed logical nodes and data objects for key equipment, including tube trailers, compressors, mid tanks, high tanks, dispensers, and valves. We developed a prototype that simulates a small-scale hydrogen refueling station environment using a Raspberry Pi and a network switch. Data modeling and communication were implemented using the libIEC61850 library, and time synchronization was performed using the IEEE 1588. We quantitatively analyzed the average and standard deviation of the transfer delay according to three data collection methods (individual, dataset, and reported) in a hydrogen refueling station using the IEC 61850 communication method. The experimental results were analyzed to compare the performances of the three data collection methods. Significant differences in transmission delay and standard deviation were observed depending on the collection method. The proposed framework can serve as the basis for the development of advanced hydrogen refueling station systems.